The relationship between communicational leaders and teachers motivation towards job performance - Mutwakil Abdellatif Fadlelmoula Elfadni
Educational leaders has a very significant role in influencing the behavior of the teachers, and in creating an effective academic atmosphere which considered an investment factor in the motivation of teachers, and educational achievement of students. This study aimed to find the relationship between the communicative skills of educational leaders and the teachers' motivation to job performance from the point of view of teachers, this study was conducted on teachers in locality of Khartoum in Khartoum state. To achieve the objectives of this research, the researcher used the quantitative method in studying the relationship between the variables in this study . The questionnaire was distributed to 480 teachers from more than 50 schools were randomly selected, 356 sets or 74% of the questionnaire were returned and analyzed using the Statistical Package for Social Science (SPSS version 18) software and (AMOS Graphic Program), data collection the statistical tests has been used to measure the credibility of the questionnaire. The finding shows that communication skills directly impact teachers' motivation and standardized coefficient were 0.853. Also this finding shows the direct impact of teachers' motivation on job performance , and the standardized coefficient was 0.581. So, the mediation effect the direct relationship between variables should be tested. So, based on the positive direct relationship between the variables, the mediation effect of teachers' motivation for the relationship of communication skills and job performance was examined, and the finding shown a significant relationship and communication skills indirectly impact job performance through their impact on teachers' motivation, and the standardized coefficient was 0.496 and was significantly more than 0.08; as well, the result reveals accept the H4. The study has come out with a number of recommendations, first, mostly on developing the teachers academically, practically and technically through the communicative skills of the leaders of educational development. Secondly, Training the education leaders on communication skills, especially writing skills, as well as the study recommended making another study to know the relationship between the communication skills of the education leaders and job satisfaction in the Sudanese schools in Sudan.